PROTECTING CITIZENS IN BORDER TERRITORY BASED ON HUMAN RIGHTS - Endah Rantau Itasari (Jurnal Pendidikan Kewarganegaraan Undiksha, 2021)
Recognition and protection of human rights is one of the characteristics of a rule of law. The State of Indonesia is a state based on law in accordance with the provisions of Article 1 paragraph 3 of the 1945 Constitution "The State of Indonesia is a constitutional state". Human rights are basic rights or citizenship that are inherent in an individual since he was born by nature which is given directly by God Almighty which cannot be deprived and deprived of its existence and must be respected, upheld, and protected by the state, law, government and everyone. for the honor and protection of human dignity. Apart from that, Indonesia is obliged to carry out protection and enforcement of human rights for its citizens because Indonesia has implemented international agreements in matters of human rights enforcement.